Challenges and Coping Strategies of Maritime Instructors and Students in An Online Distance Learning (ODL) Environment - Mundo, David Gerald S. Del; Malangen, Ardrian D.; Cruz, Orlando Dela (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
ABSTRACT The COVID-19 pandemic has forced Higher Education Institutions (HEIs), Teachers and students to move into Online Distance Learning in the Philippines to continue providing quality education. The study centers on two factors the Challenges and Coping Strategies of Maritime Instructors and Students in an Online Distance Learning (ODL) Environment of Dr. Carlos S. Lanting College. A total of 157 respondents were involved in the study and distribution of questionnaires was done thru online. The descriptive and quantitative method of research is used in this study. As a result both the students and teachers used smartphones and laptop in Online Distance Learning but majority of the students have postpaid subscription service (42.38%) with an unstable and slow internet connectivity. Furthermore, the Challenges of Maritime Instructors and Students in an Online Distance Learning (ODL) Environment, the respondents generally answered “rarely” to the given statements as to academic requirements(M=2.08 and M=2.33), Learning Management System (M=1.96 and M=2.30), delivery of instructions (M=2.17 and 2.39) while data from learning environment (M=2.78 and M=2.73) is interpreted as "sometimes," inferring that the respondents perceived the learning environment as the biggest challenge out of the four. The coping strategies of Maritime Instructors and Students in ODL the students generally answered "sometimes" to the given scenarios while the instructors generally answered "often." Meanwhile, the results show that the instructors preferred utilizing the Internet to their advantage for researching lessons and similarly to the students, setting specific time to prepare for school work are the best coping strategies for them. There is no significant difference and relationship on the Challenges and Strategies of Maritime Instructors and Students in an Online Distance Learning (ODL) Environment. Thus, to address the challenge regarding the learning environment and the poor internet connection, the findings of the study recommend that students and instructors must set time to prepare for schoolwork, create notes to better understand/deliver a lesson, and find another place for better learning/teaching and lesser distractions.